Genetically Improved Yeast Strains with Lower Ethanol Yield for the Wine Industry Generated Through a Two-Round Breeding Program - Martinez-Fernandez, C; Ganga-Munoz, M; Garcia-Mena, V; Kessi-Perez, E; Gomez-Luna, M (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
Saccharomyces cerevisiae is a species of industrial significance in the production of alcoholic beverages; it is the main species responsible for the fermentation of grape must. One of the main current problems in the wine industry is high alcohol levels caused by climate change. Pre- and post-fermentation strategies are used to reduce the alcohol content in wines; however, they are inefficient, affect organoleptic properties, face legal restrictions, and/or increase production costs, which has motivated efforts to obtain microbiological solutions. In the present work, we carried out a two-round breeding program to obtain improved yeast strains with lower ethanol yield. The trait under study showed high heritability (0.619), and we were able to lower the ethanol yield by 10.7% in just one generation. We finally obtained a population composed of 132 strains, of which 6 were used to produce wine from natural grape musts on a pilot scale, highlighting improved strains “C2-1B4” and “C7-1B7” as those that showed the best results (alcohol levels between 0.3 and 1.5% ABV less than expected). Further studies are required to understand the connection between initial sugar concentration and ethanol yield, as well as the genetic variants underlying this phenotype. © 2025 by the authors.